2020
DOI: 10.3390/toxins12080495
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Combined In Vitro Effects of Deoxynivalenol and Zearalenone on Boar Semen

Abstract: Mycotoxins deoxynivalenol (DON) and zearalenone (ZEN) can negatively affect pig health. However, little is known about their effects on boar semen. We assessed the individual and combined effects of DON and ZEN on boar semen in vitro. In a pretrial, we determined the minimum dose (MiD) of each mycotoxin that induces a significant alteration of sperm progressive motility, as investigated using computer-assisted semen analysis (CASA). In the main trial, the individual and combined effects of each mycotoxin’s MiD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…Multi-mycotoxin analysis of aflatoxins (AFB 1 , AFB 2 , AFG 1 , AFG 2 ), diacetoxyscirpenol (DAS), deoxynivalenol (DON), zearalenone (ZEN), OTA, fumonisins (FB 1 , FB 2 ) and trichothecenes (T 2 , HT 2 ) for the trial feeds was performed at an accredited testing laboratory (Agrolab RDS, Sindos, Greece), whereas feed nutritional analysis was performed in the Laboratory of Nutrition (School of Veterinary Medicine, AUTh). Mycotoxin analysis of feed was performed by LC/MS–MS following the method of Li et al [ 59 ] for fumonisins detection and Ren et al [ 60 ] for the rest of the toxins, as described by Tassis et al [ 61 ]. Detection limits were 0.5 μg/kg for AFB 1 , AFB 2 , AFG 1 , AFG 2 , 1 μg/kg for OTA, T-2, HT-2 and DAS, and 10 μg/kg for ZEN, DON, FB 1 , FB 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Multi-mycotoxin analysis of aflatoxins (AFB 1 , AFB 2 , AFG 1 , AFG 2 ), diacetoxyscirpenol (DAS), deoxynivalenol (DON), zearalenone (ZEN), OTA, fumonisins (FB 1 , FB 2 ) and trichothecenes (T 2 , HT 2 ) for the trial feeds was performed at an accredited testing laboratory (Agrolab RDS, Sindos, Greece), whereas feed nutritional analysis was performed in the Laboratory of Nutrition (School of Veterinary Medicine, AUTh). Mycotoxin analysis of feed was performed by LC/MS–MS following the method of Li et al [ 59 ] for fumonisins detection and Ren et al [ 60 ] for the rest of the toxins, as described by Tassis et al [ 61 ]. Detection limits were 0.5 μg/kg for AFB 1 , AFB 2 , AFG 1 , AFG 2 , 1 μg/kg for OTA, T-2, HT-2 and DAS, and 10 μg/kg for ZEN, DON, FB 1 , FB 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Although there are regulations set to limit the level of DON concentration in human food products (1-2 mg/kg of food) (29), masked and modified forms of DON, which are not detected by established standard methods, may lead to underreporting of mycotoxin levels in food products (62). Moreover, humans are likely exposed to varying levels of the mixtures of mycotoxins present in the different food products on a daily basis, which can have additive to synergistic toxic effects (63,64), and make it difficult to estimate the exact exposure levels. Thus, investigating the immunomodulatory effect of DON at a wide range of concentrations, including the concentrations above the established limits can be considered as highly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tassis et al [ 67 ] carried out a boar semen analysis. The authors showed that ZEN negatively affects various sperm parameters such as sperm viability and motility.…”
Section: The Occurrence Of Zen In Body Fluidsmentioning
confidence: 99%